"Die Partei der Blumen und Nachtigallen": Heine and Herder Between National and World Literature. Issue 1 (2nd January 2023) - Vaughn, Chloe
Abstract: This essay explores Heinrich Heine's importance as a thinker of world literature, his indebtedness to the work of Johann Gottfried Herder, and his key departures from the latter. By analyzing Heine's treatment of various national literatures, the essay demonstrates that his notion of world literature is characterized by an emphasis on borrowing, insertion and translation from one literary tradition to another, with a view to the enrichment of the receiving context. Heine understands world literature as both universal and locally specific (i.e., belonging to and embodying a particular Volk ), and as embedded in other disciplines and social forces. He draws heavily on Herder, who was keenly attentive to the differences that defined the various national literatures and encouraged their interaction. Heine went further than Herder, however, in his understanding of literature's place in the world, and foregrounded the political, social and economic significance of what made the literatures of the various Völker unique. Departing from the vision of harmony and integration with which he associated Herder, Heine emphasized the dissonance and spirit of competition that marked encounters between national literatures. Heine's notion of world literature relied on the generative distinctions that persist between peoples and literatures, even amid constant cultural exchange.